FLOW MODELLING AT COMPRESSOR CASCADE WITH TURBULATORS ON BLADE SURFACE - Терещенко, Юрій Матвійович; Дорошенко, Катерина Вікторівна; Терещенко, Юрій Юрійович (Science-based technologies, 2016)
The research of boundary layer control at compressor blade row is actually. It is practical interest to solve the problem of providing of gas-dynamic stability of compressors of gas turbine engines. Aim of work is to investigate the effect of the placement density of turbulators on blade surface at the loss level at the critical flow mode. Flow at airfoil cascade with different placement densities is studied in work. Roughness elements were placed at the entrance of the blade witch was 30% of the surface area of the blade. The characteristics of airfoil cascades at placement density coefficient 0.36, 0.24, 0.18 were investigated. Shape of roughness element is hemisphere. Using of roughness elements at the entrance of the blade with a placement density coefficient 0.18…0.36 lead to a decreasing in value of total pressure loss coefficient at critical flow mode from 0.084…0.12 (for cascade with smooth blades) to 0.03…0.041